Shen-Ling-Bai-Zhu-San for ulcerative colitis: Protocol for a systematic review and meta-analysis. Issue 38 (September 2018) - Yang, Long; Song, Yuanyuan; Jin, Pei; Liu, Yueyang; Wang, Yue; Qiao, Huixia; Huang, Yahui
Abstract: Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) at the colonic mucosa and submucosa. Shen-Ling-Bai-Zhu-San (SLBZS) is one of the most common formulations of traditional Chinese medicine (TCM) for the treatment of UC. However, its effects and safety remain uncertain. This protocol is described for a systematic review to investigate the beneficial effects and safety of SLBZS for UC. Methods: We will systematically search for eligible studies in PubMed, the Cochrane library, Embase, the Chinese Biomedical Literature Database (CBM), the China National Knowledge Infrastructure (CNKI), and Wanfang Data (WAN FANG) until August 2018. The primary outcomes are the induction of remission and the maintenance of remission. The summary results will be pooled using the random-effects model or fixed-effects model according to the heterogeneity of the included studies. Results: The results will be submitted to a peer-reviewed journal for publication. Conclusion: The conclusion of our systematic review will provide evidence to judge whether SLBZS is an effective intervention for patient with UC. PROSPERO registration number: PROSPERO CRD 42018100477. Abstract : Supplemental Digital Content is available in the text